A Flexible Wireless sEMG System for Wearable Muscle Strength and Fatigue Monitoring in Real Time - Qibei Gong; Xijun Jiang; Yuxuan Liu; Min Yu; Youfan Hu (Advanced Electronic Materials, 2023)
Abstract The detection of surface electromyography (sEMG) signals on the skin has attracted increasing attention because of its ability to monitor muscle conditions in a noninvasive manner and thus possesses great application potential to assess athletic status and training efficiency in real time or to evaluate postoperative muscle rehabilitation conveniently. Here, a flexible wireless sEMG monitoring system that consists of a stretchable sEMG epidermal patch and a flexible printed circuit board to provide real‐time evaluation of muscle strength and fatigue is reported. The epidermal patch is designed to have good stretchability and permeability and optimized to ensure a low contact impedance with the skin and minimized background noise for sEMG signal acquisition with high fidelity. Six commonly used time‐domain and two frequency‐domain features extracted from sEMG signals are systematically analyzed, and a strategy for feature selection and pattern identification is proposed that eventually enables the real‐time assessment of muscle strength and fatigue by using an integrated system in a wearable form.